2005
DOI: 10.1016/j.bios.2004.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Impedimetric immunosensors based on the conjugated polymer PPV

Abstract: Abstract:In the work reported here, we investigated the interaction between the semiconducting polymer MDMO-PPV and antibodies against the fluorescent dyes FITC and Cy5. The antibodies are adsorbed physically onto thin polymer films on gold electrodes, as seen in AFM images of these films. By tuning the antibody concentration, the contact angle of distilled water with the film can be made to vary between 95° and 50°, showing that different surface densities of antibody can be obtained. That these biosensor fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Finally, conjugated-polymer electrodes provide the possibility of immobilizing a vast array of indicator molecules along the surface or inside the polymer bulk. [31] As early as 1986, PPy was evaluated as the outer electrode material for neural prosthetic applications. [31] It was shown that PPy grown on the cross sections of Pt wires embedded in glass improved the charge-pulsing capacity compared to bare Pt wires, see Figure 2a.…”
Section: Electrodes For Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, conjugated-polymer electrodes provide the possibility of immobilizing a vast array of indicator molecules along the surface or inside the polymer bulk. [31] As early as 1986, PPy was evaluated as the outer electrode material for neural prosthetic applications. [31] It was shown that PPy grown on the cross sections of Pt wires embedded in glass improved the charge-pulsing capacity compared to bare Pt wires, see Figure 2a.…”
Section: Electrodes For Stimulationmentioning
confidence: 99%
“…[31] As early as 1986, PPy was evaluated as the outer electrode material for neural prosthetic applications. [31] It was shown that PPy grown on the cross sections of Pt wires embedded in glass improved the charge-pulsing capacity compared to bare Pt wires, see Figure 2a. To stimulate or record neuronal impulses, the impedance characteristics must be designed to enable signal translation between the electrode and the neuron, which usually occur at the biologically relevant frequency of ca.…”
Section: Electrodes For Stimulationmentioning
confidence: 99%
“…Throughout their history, PPVs have been used in a large variety of advanced applications, ranging from organic photovoltaic cells (OPVs), light emitting diodes (LEDs), field effect transistors (FET)s and biosensors [5,6]. Although other well-suited materials have made their way into the field of such electronic devices, PPVs are still interesting because of their high synthetic reliability and simple scale up possibilities [7], resulting in the potential high industrial relevance of these polymers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…3). Recent advances in sensor integration [4,8,16,17,22,[25][26][27]30] provide the ability to execute intelligent computer-controlled assays that obtain feedback and make decisions in real-time based on sensor readings (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%